Mineral composition in mussel Mytilus galloprovincialis and clam Tapes decussatus from Faro Lake of Messina: risk assessment for human health - Bruno, Fabio; Nava, Vincenzo; Zappalà, Sebastiano; Costa, Giovanna Lucrezia; Fazio, Francesco; Parrino, Vincenzo; Licata, Patrizia (Frontiers in Toxicology, 2024)
Bivalve are exposed to a wide range of contaminants, some of which may be toxic to human health. The aim of this study was to detect essential and non-essential elements such as Na, Ca, Mg, Cr, Mn, Fe, Ni, Cu, Zn, As, Cd, Pb, Hg, Be and Co in water, sediments, and Mytilus galloprovincialis and Tapes decussatus from Faro Lake. It is a lake of marine origin located on the northern coast of Messina (Sicily), where shellfish farming has been practiced for many years. Metals were analysed by a single quadrupole inductively coupled plasma mass spectrometer (ICP-MS), except for Hg, which was quantified using a direct mercury analyser (DMA-80). The study evaluated the nutritional intake of elements through the ingestion of clams and mussels and the potential health risks to consumers. The lead levels found in M. galloprovincialis were below the LOQ, while in T. decussatus the concentrations were below the limit indicated by European Regulation 915/2023. Statistical analysis was carried out on M. galloprovincialis and T. decussatus samples using SPSS 27 and the data showed highly significant differences between the two species (p < 0.001). Cadmium (Cd) and mercury (Hg) concentrations were also below the legal limit in all samples analyzed. This study has shown that clams and mussels are a source of sodium (Na) with a Recommended Dietary Allowance (RDA) of 36% in M. galloprovincialis and 77% in T. decussatus. The percentages obtained for calcium (Ca) and magnesium (Mg) were 17%–19% and 18%–8%, respectively. The RDA of chromium (Cr) was of 191% for M. galloprovincialis and of 405% for T. decussatus. The Fe percentages were 92% and 169% for M. galloprovincialis and T. decussatus, respectively. The concentrations of the other metals observed in the two bivalve species of Lake Faro were generally lower than the Tolerable Weekly Intake (TWI) values estimated as a risk to human health.